Incidence of meningeal enhancement on brain MRI secondary to lumbar puncture. Issue 4 (August 2016) - Wesley, Sarah Flanagan; Garcia-Santibanez, Rocio; Liang, John; Pyburn, Dewitt
Abstract: Background: Concern for reactive meningeal enhancement after lumbar puncture (LP) is a common reason for performing brain MRI prior to LP. We sought to determine actual incidence of unexplained meningeal enhancement after LP. Methods: We collected results from all contrasted brain MRIs in patients admitted to adult neurology at a New York City hospital over a 3-year period. We used electronic medical records to determine whether an LP had been done within 30 days prior to brain MRI. The control group comprised those brain MRIs not preceded by an LP within 30 days prior to imaging. Number of cases of unexplained meningeal enhancement was compared between groups using a Fisher exact test. We recorded variables such as number of LP attempts, needle size, amount of fluid removed, and days from LP to brain MRI. Results: From 2011 to 2013, there were 77 cases of LP prior to brain MRI and 707 controls (n = 784). Of the cases, 3 had meningeal enhancement, 1 (1.2%) of which was unexplained. Of the 707 controls, 36 had enhancement, and none was unexplained. The p value comparing unexplained enhancement in the cases vs controls was 0.098. Conclusions: Iatrogenic meningeal enhancement from prior LP that is not attributable to traumatic LP or intracranial hypotension is rare and not more common than in cases without a prior LP. Results suggest that the practice of delaying LP until after brain MRI might not be supported in cases where LP is necessary.